Keystroke Dynamics on Android Platform. (2015) - Antal, Margit; Szabó, László Zsolt; László, Izabella
Abstract: Currently people store more and more sensitive data on their mobile devices. Therefore it is highly important to strengthen the existing authentication mechanisms. The analysis of typing patterns, formally known as keystroke dynamics is useful to enhance the security of password-based authentication. Moreover, touchscreen allows adding features ranging from pressure of the screen or finger area to the classical time-based features used for keystroke dynamics. In this paper we examine the effect of these additional touchscreen features to the identification and verification performance through our dataset of 42 users. Results show that these additional features enhance the accuracy of both processes.